Agglomeration of acacia mangium biomass - Quyen, Trinh Van; Nagy, Sándor (Vietnam Journal of Science and Technology, 2018)
The aim of this study is to analyze the effects of temperature (T), moisture content (MC) and particle size (x) on Acacia mangium biomass and also to find the optimal conditions of the densification process for producing tablet with high density. The result shows that at constant pressure, increasing temperature (T) resulted in higher density of tablets and also increasing moisture content resulted in higher density of tables. Tablets made from raw material with smaller particle size have lower strength than those made from material with larger particle size.